Sigortacılıkta Risk Yönetimi - Erşen,İlker (Sosyal Bilimler Enstitüsü, 1992)
Birinci ve ikinci bölümlerde risk ile risk yönetimi kavramları üzerinde durulmuştur. Üçüncü bölümde risklerin tanımlanması, ölçü mü/değerlendirilmesi anlatılmıştır. Bu bölüm içerisinde risklerin tanımlanmasında kullanılan yöntemler sıralandıktan sonra riskin ölçümünde kullanılan hasarın frekans ve şiddeti incelenmiş, hasarın ölçülmesinde kullanılan olasılık dağılımlarının özelliklerinden bahsedilmiştir. Dördüncü bölümde sigortacılıkta fiyatlandırma ve Türkiye'de sigorta hizmetlerinin fiyatlandırılması ele alınmıştır. Beşinci bölümde riskin kontrolü ve finansmanı anlatılmıştır. Altıncı bölümde örnek bir risk yönetimi uygulamasına yer verilmiştir.

Risk management as a subject and as a function of business management is relatively new and its precise boundaries are still the sub ject of much debate. It may be defined as the minimization of the adver se effects of risk at minumum cost through its identification, measure ment and control. There is no single generally accepted definition of the word risk. For example risk has been defined as the subject of insuran ce, chance of loss, uncertainly concerning the outcome. Risks can be devided into two broad groups according to the outcome of uncertain events. Speculative risks are those that offer the firm chance of gain or loss. Pure risks are those risks where the occurence of the event results at the best in no change of gain in the situation of organization exposed to risk. Risk management is concerned with pure risks. The risk manager's role is limited to dealing with the pure risks to which the organization is exposed or extend to some of the spe culative risks. A risk manager must gain the co-operation of all colleagu es who possess information he requires and whose help is needed for carrying out risk handling decisions. There will be a more frequent, direct relationship with legal, finance, production and personel depart ments. Risk managers in large firms keep records of various sorts. Amongs the most important are lists of insurance contracts, including their expiration dates, valuation records showing the value and location of all property in which the firms has a financial interest, personel records on the firm's employees. The risk management department must also relate to outsiders who help perform the risk management function or create additional exposures through services provided other depart ments. The first step in risk management is to identify the various types of potential losses confronting the firm, the second is to measure these patential losses with respect to such matters as their likelihood of occurence and their probable severity. Risk identification requires a knowledge of the organization, the market in which it operates the legal, social, economic and political IX environment, its financial strengths and weaknesses, its vulnerability to unplanned losses, the manufacturing processes and the management systems and business mechanism by which it operates. Checklist of potential losses are often used to identify risks and they will need to cover: - all types of assets which it may be responsible. The list cover not only obvions physical assets but also intangible assets and person nel. - sources of exposure to loss producing events. The possible exposures to loss are classified as direct exposu res, indirect or consequential as direct exposures, indirect or consequen tial exposures, net income exposures and liability exposures Six methods that have been suggested for application of check list are; - The risk analysis questionnaire, contains a list of questions to remind the risk manager of possible loss exposures, to gather informa tion that will describe in what way and to what extent the particular busi ness is exposed to that patential loss, and summarize to existing insuran ce program including premiums paid and losses incurred. - The financial-statement method: Under this method each account title is studied in depth to determine what potantial losses it creates by analyzing the balance sheet, operating statements and suppor ting records, the risk manager can identify all the existing property, liabi lity, and personnel exposures of the firm. - The flow-chart method: A flow chart shows all the operati ons of the firm, starting with raw materials and other inputs at suppliers locations and ending with finished products in the hands of customer. The checklist of potantial property, liability, and personel losses is appli ed to each property and operation shown in the flow chart to determine which losses the firm faces. - On-site inspections are a must for the risk manager. - Statistical records of losses and analysis of the enviroment are also used to determine patential risks. The strategy of the management must be to employ one of the se methods or combination of methods that best fits the situation at hand. The choice is a function of the nature of the business, the size of the business and the availability of in-house expertise. For example, pub lished checklists and outsiders (insurance agents, brokers, risk manage ment consultans) are used more frequently by smaller firms that cannot afford to have the task done by specialist in their own management structure. Large-firms with a more scphisticated risk management depart ment may show more originality in identification procedures. Risk measurement: Risk measurement has two dimensions; - the loss frequency or the number of losses that will occur, - the severity of those losses. Both loss-frequency and loss severity data are needed to evalu ate the relative importance of an exposure to potantial loss. The impor tance of an exposure to loss depends mostly upon the potantial loss seve rity, not the potantial frequency. A potential loss with catastrophic possibilities, although infre quent, is for more serious than one expected to produce frequent small losses and no large losses. On the other hand, loss frequency cannot be ignored, if two exposures are characterized by the some loss severity, the exposure whose frequency is greater should be ranked more impor tant. Probability distributions make possible more comprehensive risk measurements than the techniques mentiened above, and they are becoming a more common tool of modern management. Probability dis tributions deal with three different ways of measuring loss experience (1) total dollar losses per year, (2) the number of occurrences per year, and (3) the dollar losses per occurence. After the risk manager has identified and measured the risks facing the firm, he or she must decide how to handle them risk control measures include; (1) avoidance, (2) risk reduction (3) separation (4) combination and (5) some transfers. Risk avoidance is the most drastic method of dealing with risks. Whereas other methods are aimed at reducing the potantial impact of those risks to which an organization is exposed, succesful risk avoidence results in the total elimination of exposure to loss due to a XX specific risk, however, it is also the method of most limited practical application because it often involves abandoning some activity and so losing the benefits that acompany it. Risk reduction is concerned with achieving a reduction in either the probability of a loss producing event occurring or in the size of the ensuing losses. Separation of the firm's exposures to loss instead of concentra ting them at one location where they might be all be involved in the same loss is the third risk control tool for example, instead of placing its entire inventory in one warehouse, a firm may separate this exposure by placing them in more than one werehouse. Combination makes loss experience more predictable by incre asing the number of exposure units. The difference is that unlike separa tion, which spreads a specified number of exposure units, combination increases the number of exposure units under the control of the firm. Transfer can be accomplished in different ways. For example, the property or activity responsible for the risk may be transferred to other persons or organization. The risks remaning after the risk control measures have been implemented will be financed. The sources of finance available to a firm may be cllassified in several ways. Postloss financing-preloss financing categorization is one of them. Postloss financing is defined by the secu- rement of funds after the loss. The financing arrangements are responsi ve (to the loss) rather then anticipatory and the costs of raising finance are born after the loss (Cash and marketable securities, debt and equ ity...) In contrast to postles financing, preloss financing is secured by arrangements made and costs borne in anticipation of loss. The most obvious example is insurance which is secured by the prior payment of an insurance premium. The opportunity cost for this form of financing is incurred with the payment of the premium, not with the occurence of loss. A further example is a "self insurence" fund into which premiums are paid and from which losses are financed. The grounds on which a decision to buy insurance will be taken can be summarised as: - the potential size and frequency of losses: If there is such a high frequency and low severity of losses that they can be predicted with a very high degree of certainty, there is no risk and no point in insuring. Insurance is best suited to risks with low frequency and high loss severity. xn - the size of the premimum loading; the larger the loading the more incentive an organization will have to retain its own risks. - the value that the organization places upon financial certa inty. Other reasons for purchasing insurance: - risk reduction services - risk financing and other advice - claims handling services
Risk Management In Insurance
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1992
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 1992
Keywords: Sigortacılık; Fiyatlandırma; Risk yönetimi; Sigorta hizmetleri; Insurance; Pricing; Risk management; insurance services